Sudden Bilateral Hearing Loss After Cervical and Ocular Vestibular Evoked Myogenic Potentials. Issue 6 (July 2015) - Mattingly, Jameson K.; Portnuff, Cory D. F.; Hondorp, Brian M.; Cass, Stephen P.
Abstract : Objective: Cervical and ocular vestibular evoked myogenic potentials (cVEMPs and oVEMPs) are commonly used in evaluation of neurotologic disorders. We present a case of sudden bilateral hearing loss immediately after oVEMP and cVEMP testing. The hearing loss did not recover. To our knowledge, no previous case reports discuss sudden hearing loss, especially bilateral, associated with VEMP testing. Patient: A single patient with sudden bilateral hearing loss that has persisted after cVEMP and oVEMP. Intervention: The patient had a history of chronic daily dizziness. She underwent vestibular function testing that included cVEMP and oVEMP testing. A significant bilateral sensorineural hearing loss was noted immediately after cVEMP and oVEMP testing and confirmed with audiometric testing. Despite the use of oral steroids, her hearing loss did not recover. Main Outcome Measures: Serial audiograms, calculated maximum total sound energies to each ear. Results: Pre-VEMP versus post-VEMP audiograms show increased thresholds and decreased word recognition scores; total sound energy delivered to each ear shows significant sound exposure. Conclusion: Although VEMP testing is thought to be safe and well tolerated, a significant amount of sound can be delivered to the cochlea, and certain individuals may be susceptible to acoustic trauma at these levels. We recommend limits for VEMP stimuli levels and attention to total sound exposure when multiple trials are used.